Physical properties analysis of UV-Crosslinked sulfonated Poly Ether Ether Ketone and Methyl Cellulose / Nordiana Nabilla Ramly … [et al.] - Nabilla Ramly, Nordiana (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2016)
Proton exchange membrane materials based on sulfonated Poly Ether Ether Ketone with Methyl Cellulose are developed in this study. The hybrid membrane is exposed to UV radiation with photoinitiator to improve the membrane dimensional stability up to 50%. The hybrid membranes characterized by FTIR shows the crosslinking occurs by formation of C-C bond from BEE instead of the consumption of SOJH group. This new cross linked hybrid membrane shows good prospect for the use as proton exchange membrane in fuel cell.